1989
DOI: 10.1002/eji.1830191005
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory cerebrospinal fluid t cells have activation requirements characteristic of cd4+cd45ra t cells

Abstract: It has long been recognized that T cells in the cerebrospinal fluid (CSF) and other inflammatory compartments cannot be stimulated by mitogen and the reason for this has remained unknown. This question was investigated using mononuclear cells (MNC) isolated from the CSF of subjects with multiple sclerosis and other inflammatory brain diseases which predominantly express the CD4 and CDw29 but not CD45RA determinants. CSF and blood cells were stimulated by either the CD3/T cell receptor complex, the CD2 activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 28 publications
3
4
0
Order By: Relevance
“…granulocytes, monocytes, MyDCs, basophils and CD56 dim NK cells) and B cells are proportionally under-represented in the CSF, while T cells (especially CD4+), immunoregulatory CD56 bright NK cells and PlDCs are over-represented. We confirmed that T and B cells in the CSF have more activated phenotype than analogous cells in the blood, an observation that was previously attributed to selective ability of activated lymphocytes to cross the blood brain barrier (BBB) (24). We expand these findings by demonstrating that CSF T cells not only express more activation markers such as HLA-DR, but they are also significantly and uniformly degranulated in comparison to their blood counterparts.…”
Section: Discussionsupporting
confidence: 83%
“…granulocytes, monocytes, MyDCs, basophils and CD56 dim NK cells) and B cells are proportionally under-represented in the CSF, while T cells (especially CD4+), immunoregulatory CD56 bright NK cells and PlDCs are over-represented. We confirmed that T and B cells in the CSF have more activated phenotype than analogous cells in the blood, an observation that was previously attributed to selective ability of activated lymphocytes to cross the blood brain barrier (BBB) (24). We expand these findings by demonstrating that CSF T cells not only express more activation markers such as HLA-DR, but they are also significantly and uniformly degranulated in comparison to their blood counterparts.…”
Section: Discussionsupporting
confidence: 83%
“…4A). Because our data and several previous reports have suggested that CSF cells from MS patients are primed memory cells that express high levels of CXCR3 and have effector functions, we postulated that these cells would rapidly convert into T EM after stimulation (24)(25)(26)(27). Indeed, upon stimulation in vitro, we found that the CSF cells from MS patients rapidly became CCR7 Ϫ at day 7 and maintained this phenotype at day 14 ( Fig.…”
Section: Ms Brain Tissuesupporting
confidence: 63%
“…In both cases, mitogenic unresponsiveness appears to be due to the lack of appropriate co-stimuli. That is, the mitogenic activity of T cells isolated from multiple sclerosis patients was restored with PMA (43), and optimal mitogenic responses by the encephalitogenic rat T cell line were observed only in the presence of nonfractionated SPL (5). In a similar manner, the lack of responsiveness of T HyB-2 hybrids to PMA and ionomycin may be associated with their requirement for co-stimulatory molecules on RS-NAdh SPL.…”
Section: Resultsmentioning
confidence: 92%
“…This possibility is supported by the observation that target organs affected in different autoimmune diseases such as the cerebrospinal fluid of patients with multiple sclerosis, the synovial fluid of patients with rheumatoid arthritis, or peripheral blood of patients with systemic lupus erythematosis are populated by T cells lacking normal responsiveness to mitogens (40)(41)(42)(43). In a similar manner, an encephalitogenic line of rat Thelper cells also was refractory to stimulation with the mitogen Con A even when these cells were cultured with splenic macrophages (5).…”
Section: Resultsmentioning
confidence: 98%